Experimental mechanical-damage assessment of earthen mixes reinforced with micro polypropylene fibers. (20th February 2019) - Araya-Letelier, G.; Concha-Riedel, J.; Antico, F.C.; Sandoval, C.
Graphical abstract: Highlights: Addition of MPPF to earthen materials control restrained drying shrinkage cracking. Impact strength and flexural toughness increase as fiber dosage increases. Compressive and flexural strength are not statistically affected. Abstract: The addition of engineered polypropylene fibers to earthen materials offers new opportunities to control their damage evolution and mechanical properties that altogether provides more reliability and extends the life span of these materials. The latter is of special interest considering that earthen materials are still widely used in the form of adobe blocks for earthen masonry, cob, rammed earth or even earthen mortars for new construction and conservation of historic buildings. In this work, the effect of dosage of micro polypropylene fibers (MPPF) in the damage-mechanical performance of earthen mixes is studied experimentally. Part of the experiments includes two different tests to assess distributed and localized cracking of reinforced earth subject to restrained drying shrinkage. In addition, the experimental results showed that the incorporation of MPPF increases up to 83 times the impact strength and 11 times the flexural toughness of earthen mixes. Other mechanical properties such as compressive and flexural strength are not statistically affected by the incorporation of MPPF.